Penerapan Kebijakan Zakat Sebagai Unsur Pengurang Pajak Penghasilan Di BAZNAS Kabupaten Jombang - Lestari, Devi Ayu; Fajar, Fajar (Universitas Sebelas Maret, 2023)
Zakat and taxes are two obligations to be paid by Muslim citizens. Both are paid when an individual is declared eligible to be declared taxable and zakat obligatory. However, the similarity causes zakat and to be a considered as a double burden for Muslim taxpayers. Therefore, the government has designed a policy to accommodate zakat as an element of income tax reduction. Zakat payments may be deducted from taxable income on the condition that they are paid through an administrative body of zakat that has been validated by the government, with a report in the annual SPT, and include other valid evidence. The purpose of this research is to find out the application of zakat as an element of income tax reduction in BAZNAS Jombang. The analysis used is a descriptive method with a qualitative approach. The results of the research show that the implementation of the zakat policy as an element of income tax reduction in BAZNAS district, Jombang, has not been optimally implemented. This is due to the lack of public awareness of the importance of paying the pledge, so this policy has not received a positive response among the public. Besides, the lack of socialization between stackholders in this case is due to BAZNAS and the tax directors lack of socialization of this policy towards society. To deal with it, it requires a high level of enthusiasm and cooperation among stakeholders so that this policy can be implemented optimally.